An innovative eco-friendly optical sensor designed specifically to detect gallium ions in environmental samples - Mahmood D. Aljabri; Salah M. El-Bahy; Refat El-Sayed; Khaled F. Debbabi; Alaa S. Amin; Naglaa M. Mohamed (Sensing and Bio-Sensing Research)
A novel membrane optical sensor with high selectivity and sensitivity was developed for detecting ultra-low concentrations of gallium (Ga3+) ions. This sensor utilized a newly synthesized compound, 4,4′-1,3-pHenylene bis(azanylyli-dene) bis(methanylylidene))bis(N,N-dimethylaniline) (PBABMBD), as its ionophore, combined with 9-(diethylamino)-5-(octadecanoylimino)-5H-benzo[a] phenoxazine (ETH-5294) as a chromoionophore within a polyvinyl chloride (PVC) membrane matrix. The impact of various parameters on the fabrication of the optical sensor and its ability to detect Ga3+ ions was thoroughly examined and fine-tuned for optimization. Demonstrating a broad linear dynamic range from 6.25 × 10−9 to 3.75 × 10−6 M, the sensor boasts impressive detection and quantification limits of 1.75 and 6.00 × 10−9 M Ga3+ ions, respectively. Furthermore, the sensor demonstrates a swift response time of just 3.0 min and can undergo multiple rejuvenations with 0.25 M HNO3 solutions. The study examined the impact of potential interfering ions on the detection of Ga3+ions. Fortunately, the results showed that the created optical sensor was very selective for Ga3+ ions and barely reacts with other anions and cations, especially indium (III). Furthermore, the sensor proved effective in accurately detecting Ga3+ ions across a range of samples, including food, alloys, water, and biological specimens.